Pattern of Antibiotic Resistance in E. coli and Klebsiella Bacteremia in Renal Transplant Recipients from Developing Country. (July 2018) - Dodani, Sunil Kumar; Nasim, Asma; Aziz, Tahir; Rizvi, Adib
Abstract : Introduction: Antimicrobial resistance has become a major public threat. Resistance to commonly used antibiotics has increased in Pakistan. Cephalosporins and ciprofloxacin resistance in E.coli have been reported in the range of 70% and 80%. Increasing resistance to ceftriaxone and Ciprofloxacin have also been reported among hemodialysis patients for Klebsiella bacteremia from our center. There is no data about antibiotic susceptibility among common gram negatives from renal transplant recipients from our country which are vulnerable population due to immunosuppressive drugs. This study is conducted to find the trends in antimicrobial resistance pattern among common gram negatives over a 9-year period in renal transplant recipients. The aim is to guide the physicians regarding decision over empirical antimicrobial choices. Methods: Our institute is a 700-bedded tertiary care hospital in a developing country where more than 5500 patients have been received transplant till now. A retrospective computerized data review of blood cultures collected from renal transplant recipients admitted in transplant unit over alternate years i.e. 2008, 2010, 2012, 2014, 2016 was conducted. Data on E.coli and Klebsiella was taken as they are the major causative microorganism identified. The resistance pattern of ceftriaxone, piperacillin-tazobactam, ciprofloxacin, amikacin and imipenem were compared over the 9 years period. Results: Of 13, 736 blood cultures, 1799 (13%) had at least one identified pathogen. E. coli (22%) and Klebsiella (6.28%) are most common pathogen among gram negatives. Ceftriaxone resistance is increased in E. coli (from 48% to 70.5%) and in Klebsiella upto 81%, whereas Ciprofloxacin resistance in both organism is in the range of 60-70%. Carbapenem resistance is also started increasing for both organism. Trends in resistance to E. coli and Klebsiella is shown in figure1 and figure 2 respectively. Conclusion: Resistance to broad spectrum antimicrobials has been increased significantly with a five-fold increase in imipenem resistance over the last 9 years. We need a robust stewardship program for judicious use of antimicrobials and better infection control measures to contain increasing resistance.